Wartime Writings, or the Imaginary Lover of Marguerite Duras - Bethany Ladimer (Studies in 20th & 21st Century Literature, 2009)
The publication in 2006 of Marguerite Duras’s Cahiers de la guerre, ‘Wartime Writings,’ written between 1943 and 1949, made accessible to the reader the first known versions of the family drama that was to become the material of much of her fiction. As this work now takes its place as chronologically first in the intertext of Duras’s autofictional writings, it sheds considerable light on our understanding of the transformations in these texts that occurred over her lifetime. Whereas L’Amant had been presented and accepted as the disclosure of a real occurrence and the origin of the other works, it presents several significant aspects of Duras’s life at the time, as well as the lover himself, in a way that is not verifiably real. The “Cahiers” help establish the difference between the verifiably real and that which seems most true about herself to the author in later life when she fictionalizes her own coming of age. The first “Cahier” holds the key to understanding the exigencies that led to the invention of the character of the Chinese lover, as it reminds us that there is no moment before legend and story-telling, and that individual memory is always constructed imaginatively.
Keywords: wartime literature; Marguerite Dura; Cahiers de la guerre; wartime writings; autofiction; identity; Cahier; legend; real; imagination; memory